OVERCOMING INTERNALISED PHOBIA AMONG BUDDHIST SEXUAL MINORITIES THROUGH MINDFULNESS. Issue 2 (3rd July 2018) - Cheng, Fung Kei
ABSTRACT: When heterosexuality dominates sexual culture, sexual minorities are marginalised, yielding minority stress and internalised phobia which devastate psychological well-being and raise suicide risks. A growing trend in using mindfulness-related interventions in health care shows positive signs, but there is a paucity of research on mindfulness for sexual minorities. This qualitative research, through interpretative phenomenological analysis, looks into how Buddhist sexual minorities (from various countries) interpret mindfulness from which their increased self-awareness, self-esteem and self-acceptance become prominent intrinsic resources, resulting in enhanced mental health and quality of life. Such an exploratory study extends the horizon of health care benefits for helping professionals and sexual minorities with alternative views in overcoming external and internalised phobia.